Ordinances, of the Town of Columbia, (S. C.) Passed Since the Incorporation of Said Town: To Which are Prefixed, the Acts of the General Assembly, for Incorporating the Said Town, and Others in Relation Thereto, at 75-76, Ordinance no. 57 (1823) - (:unkn) unknown (General Publisher, 1823)
no merchant, retailer, dealer in powder, or any person or persons whatever, within the said town, shall retain, keep or have in his, her or their possession, at any time, a greater quantity of gunpowder than fifty pounds weight.
--
Keywords: GUN POWDER STORAGE